Increased Mortality Among Renal Transplant Patients With Invasive Pulmonary Aspergillus Infection - BALCAN, MEHMET BARAN (SAGE PUBLICATIONS INC, 2018)
Introduction: Renal transplantation is the most effective and preferred definite treatment option in patients with end-stage renal disease. Due to long-term immunesuppressive treatment, renal transplant recipients become vulnerable to opportunistic infections, especially to fungal infections. Method: This was a single-center, retrospective observational study of 438 patients who underwent renal transplantation between 2010 and 2016. Results: Thirty-eight renal transplant recipients who had lower respiratory tract infection with median age of 41.5 years were evaluated for invasive pulmonary aspergillus (IPA). Of these, 52.6% were female and 84.2% had living donors. Eleven of 38 lower respiratory patients were found to have IPA infection, 5 with proven infection. Compared to patients who did not have fungal pulmonary infection, patients with invasive aspergillus were older and had high fever, galactomannan levels, and leukocyte counts. Mortality was also higher in those patients. Having fever at the baseline and IPA infection was significantly associated with mortality in univariate analysis and remained related in multivariate model after adjustment for age, gender, and fever. Conclusion: Invasive pulmonary aspergillus infection is highly associated with increased mortality rates in renal transplant patients. Fungal pulmonary infections in immune-suppressed patients should be diagnosed and treated immediately in order to avoid the life-threatening complications and may greatly improve prognosis.
Keywords: bacterial infections and mycoses; kidney transplant recipient; body regions; therapeutics; mortality; duration; FUNGAL-INFECTIONS; RECIPIENTS; EPIDEMIOLOGY; DISEASE